(untitled) (Homoeopathy for All, 2024)
Anxiety is an emotion characterized by feelings of tension, worried thoughts and physical changes like increased blood pressure. Anxiety is the natural response of body to stress. Experiencing occasional anxiety is a normal part of life. However, people with anxiety disorders frequently have intense, excessive and persistent worry and fear about everyday situations. Anxiety disorders form a category of mental health diseases that lead to excessive nervousness, fear, apprehension, and worry. Often, anxiety disorders involve repeated episodes of sudden feelings of intense anxiety and fear or terror that reach a peak within minutes. These disorders alter how a person processes emotions and behave, also causing physical symptoms. Mild anxiety might be vague and unsettling, while severe anxiety may seriously affect day-to-day living.